2010
DOI: 10.1121/1.3458857
|View full text |Cite
|
Sign up to set email alerts
|

Speech-on-speech masking with variable access to the linguistic content of the masker speech

Abstract: It has been reported that listeners can benefit from a release in masking when the masker speech is spoken in a language that differs from the target speech compared to when the target and masker speech are spoken in the same language [Freyman, R. L. et al. (1999). J. Acoust. Soc. Am. 106, 3578-3588; Van Engen, K., and Bradlow, A. (2007), J. Acoust. Soc. Am. 121, 519-526]. It is unclear whether listeners benefit from this release in masking due to the lack of linguistic interference of the masker speech, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 24 publications
7
93
0
Order By: Relevance
“…There is evidence that unattended speech is processed at least to some extent linguistically (e.g., Cherry, 1953). This linguistic processing of unattended speech impacts the processing of the to-be-attended speech stream (e.g., Brungart et al, 2001;Carhart et al, 1969;Freyman et al, 1999), as understandable maskers influence the recognition of to-be-attended speech more than speech maskers that are not understandable (e.g., Calandruccio et al, 2010;Freyman et al, 1999;Van Engen and Bradlow, 2007). This raises the possibility that to-beignored (i.e., masker) words could compete for recognition with the words in the to-be-attended (i.e., target) speech stream, therefore interfering with their recognition.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that unattended speech is processed at least to some extent linguistically (e.g., Cherry, 1953). This linguistic processing of unattended speech impacts the processing of the to-be-attended speech stream (e.g., Brungart et al, 2001;Carhart et al, 1969;Freyman et al, 1999), as understandable maskers influence the recognition of to-be-attended speech more than speech maskers that are not understandable (e.g., Calandruccio et al, 2010;Freyman et al, 1999;Van Engen and Bradlow, 2007). This raises the possibility that to-beignored (i.e., masker) words could compete for recognition with the words in the to-be-attended (i.e., target) speech stream, therefore interfering with their recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on speech-in-speech perception have shown that the intelligibility of the target speech is further reduced when the background speech is produced in a known language rather than when it is spoken in an unknown language (Van Engen and Bradlow, 2007;Calandruccio et al, 2010aCalandruccio et al, , 2010bBrouwer et al, 2012;Gautreau et al, 2013) (see Table 1). For example, Van http://dx.doi.org/10.1016/j.specom.2015.02.004 0167-6393/Ó 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, Calandruccio et al (2010a) manipulated the degree of signal intelligibility within 5 different types of babble in English and Mandarin. For this manipulation, the authors used 3 intermediate intelligibility conditions in addition to the 2 extreme conditions (English vs. Mandarin 2-talker babble) that were previously used by Van Engen and Bradlow (2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, if the masking speech is not in the same native language as the target speech (Ng et al, 2014), and if the nonnative language is linguistically dissimilar the masking effect becomes less pronounced (Brouwer et al, 2012). Two languages that belong to the same language family, will be more alike because these languages will have similar temporal and spectral properties (Calandruccio, Dhar, & Bradlow, 2010). It is also of importance if the speaker of the signal and the speaker of the masker are of the same sex, since male and female voices are less confusable (Freyman, Balakrishnan, & Helfer, 2004).…”
Section: Listening In Noisementioning
confidence: 99%